2021
DOI: 10.3928/1081597x-20210115-01
|View full text |Cite
|
Sign up to set email alerts
|

Visual and Tomographic Outcomes of a 300° Arc-length ICRS Implantation in Moderate to Advanced Central Keratoconus

Abstract: To assess the outcomes of implanting a new 300° arc-length intrastromal corneal ring segment (ICRS) in moderate to advanced central hyperprolate keratoconus.Methods: Forty-two eyes with moderate to advanced central hyperprolate keratoconus were evaluated before and after implanting an inferior 300° ICRS (AJL Ophthalmic). The clinical measurements taken included manifest refraction, uncorrected (UDVA) and corrected (CDVA) distance visual acuity (logMAR scale), and corneal tomographic analysis (Sirius; Costruzio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…However, in the current study with a short-arc-length ICRS, the flattening in the minimum K was around 1.0 D, whereas in the study by Tzelikis et al 23 with a 340-degree long-arc-length ICRS, the reduction was higher (around 3.0 D). These results could suggest that similar to what occurs for keratoconus treatment, 29 the long-arc-length ICRS could be a better indication for those post-DALK cases, which require a significant corneal flattening in both K minimum and maximum readings and, in this way, decrease corneal prolatism. By contrast, a short-arc-length ICRS should be indicated for those cases with high astigmatism.…”
Section: Discussionsupporting
confidence: 53%
“…However, in the current study with a short-arc-length ICRS, the flattening in the minimum K was around 1.0 D, whereas in the study by Tzelikis et al 23 with a 340-degree long-arc-length ICRS, the reduction was higher (around 3.0 D). These results could suggest that similar to what occurs for keratoconus treatment, 29 the long-arc-length ICRS could be a better indication for those post-DALK cases, which require a significant corneal flattening in both K minimum and maximum readings and, in this way, decrease corneal prolatism. By contrast, a short-arc-length ICRS should be indicated for those cases with high astigmatism.…”
Section: Discussionsupporting
confidence: 53%
“…However, considering that posterior corneal aberrations increase in advanced keratoconus, it should be expected that the posterior coma-like and spherical aberrations were significantly higher before surgery. Besides, our research group has recently shown that long-arc-length intrastromal corneal ring (ICRS) implantation provides significant changes in the anterior and posterior corneal surface morphology of moderate-advanced keratoconus, becoming both surfaces more regular ( 27 ). Although both, ICRS and Neoring, have different indications and mechanisms of action, it seems plausible to expect that Neoring might also have a regularization effect on the recipient bed.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] ICRS has been shown to be very effective in all keratoconus stages; however, it is less effective in more advanced cases. [8][9][10] The advanced keratoconus, on the other hand, requires a more invasive approach, such as deep anterior lamellar keratoplasty (DALK) or penetrating keratoplasty (PK). 11,12 Recently, a new surgical treatment has been described: corneal allogeneic intrastromal ring segment or CAIRS, [13][14][15][16] which refers to the use of any form of allogeneic tissuefresh, preserved, processed donor stroma, placed within intrastromal corneal channels.…”
mentioning
confidence: 99%
“…5–7 ICRS has been shown to be very effective in all keratoconus stages; however, it is less effective in more advanced cases. 8–10 The advanced keratoconus, on the other hand, requires a more invasive approach, such as deep anterior lamellar keratoplasty (DALK) or penetrating keratoplasty (PK). 11,12…”
mentioning
confidence: 99%